Cross-ancestry genome-wide association analysis of corneal thickness strengthens link between complex and Mendelian eye diseases - Adriana I. Iglesias; Aniket Mishra; Veronique Vitart; Yelena Bykhovskaya; René Höhn; Henriët Springelkamp; Gabriel Cuellar-Partida; Puya Gharahkhani; Jessica N. Cooke Bailey; Colin E. Willoughby; Xiaohui Li; Seyhan Yazar; et al. (Nature Communications, 2018)
Reduced central corneal thickness (CCT) is observed in common eye diseases as well as in rare Mendelian disorders. Here, in a cross-ancestry GWAS, the authors identify 19 novel genetic loci associated with CCT, a subset of which is involved in rare corneal or connective tissue disorders.